2021
DOI: 10.18632/aging.203578
|View full text |Cite
|
Sign up to set email alerts
|

Allicin protects against myocardial I/R by accelerating angiogenesis via the miR-19a-3p/PI3K/AKT axis

Abstract: Objectives: Allicin is an allyl 2-propenethiosulfinate or diallyl thiosulfinate acid with cardioprotective effects in myocardial ischemia/reperfusion (MI/R) injury. This study aims to examine the underlying mechanism by which Allicin protects against MI/R. Methods: C57BL6 mice were subjected to either sham or MI/R surgery, and mice in the Allicin group were injected with Allicin (5 mg/ml) before the induction of ischemia. The cardiac function and histopathology of experimental mice were evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Furthermore, inflammatory cytokines can stimulate myofibroblast activation and cause excessive collagen accumulation resulting in cardiac fibrosis [ 36 , 37 ]. Interestingly, several studies show that short-time I/R (2-24 h) can significantly increase expression of collagen I/III (1.5-fold) and fibrotic area (about 15-25-fold) in the myocardial tissues of rats or mice compared with sham control [ 38 40 ], suggesting that increased collagen production is an early event during myocardial I/RI. Consistent with these data, our results further confirmed that I/R for 24 and 72 h also markedly increased expression of cardiac collagen I, collagen III, and ɑ-SMA and fibrotic area compared with sham control, and this effects were greatly inhibited in RGDS-treated hearts (Figures 4(d) and 4(e) ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammatory cytokines can stimulate myofibroblast activation and cause excessive collagen accumulation resulting in cardiac fibrosis [ 36 , 37 ]. Interestingly, several studies show that short-time I/R (2-24 h) can significantly increase expression of collagen I/III (1.5-fold) and fibrotic area (about 15-25-fold) in the myocardial tissues of rats or mice compared with sham control [ 38 40 ], suggesting that increased collagen production is an early event during myocardial I/RI. Consistent with these data, our results further confirmed that I/R for 24 and 72 h also markedly increased expression of cardiac collagen I, collagen III, and ɑ-SMA and fibrotic area compared with sham control, and this effects were greatly inhibited in RGDS-treated hearts (Figures 4(d) and 4(e) ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the antioxidant effects of allicin could contribute to increasing the half-life of the vasoactive metabolites such as NO, and therefore to the maintenance of the vasodilatory actions. Additionally, the cardioprotective effects of allicin have been evidenced in the prevention of apoptosis of ischemic areas, as well as the induction of angiogenesis, which could be useful for the treatment of myocardial infarction, one of the first death causes worldwide [ 2 , 3 , 75 , 77 , 79 , 81 ]. The antiapoptotic and angiogenic activities of allicin may be useful to restore blood flow inducing recovery of injured areas and the effects on the modulation of expression and function of ion channels open the possibility of the use of allicin as an antiarrhythmic agent and pro-angiogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that allicin improved cardiac function, and reduced the myocardial infarct area, fibrosis, degeneration, necrosis and inflammatory cell infiltration in myocardial tissue as shown in experimental models of ischemia-reperfusion injury [ 77 , 79 , 80 , 81 ]. The cardioprotection induced by allicin was mediated by restoring the levels of SOD, CAT, GPx, and MDA in the myocardial tissue of rats [ 79 ].…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Activation of the PI3K/AKT signaling pathway has been shown to contribute to cell proliferation in several diseases. 23,24 In addition, it has also been reported that miR-503 can inhibit MCT-induced PH in rats. 20 Therefore, we explored the potential interactions between miR-503 and PI3K.…”
Section: Mir-503 Inhibited Pasmcs Migration and Proliferation By Inhi...mentioning
confidence: 97%